New understandings of the sea spray effect and its impact on bioavailable radiogenic strontium isotope ratios in coastal environments. (October 2020) - Alonzi, Elise; Pacheco-Forés, Sofía I.; Gordon, Gwyneth W.; Kuijt, Ian; Knudson, Kelly J.
Highlights: Coastal plants take up marine-derived strontium in a patterned but variable manner. Plants adjacent to the coast show the least input from marine-derived strontium. Morphology of the sea spray droplet cloud is likely a factor in creating this variability. Results highlight variability in 87 Sr/ 86 Sr in a coastal area. Strontium isotope baseline sampling must be intensified worldwide in coastal areas. Abstract: Archaeological chemists compare the radiogenic strontium isotope ratios of humans to those of the environment in order to assess paleomobility in contexts across the world, spanning from periods before modern humans to current forensic applications. These methods rely on the variability of bioavailable strontium isotope ratios that is typically attributed to the age and composition of the geology, among other environmental factors. One such factor, the Sea Spray Effect, refers to the homogenizing impact of marine strontium on the radiogenic strontium isotope ratios found in terrestrial settings that are incorporated into the human diet by eating coastal foods. This paper explores the impact of sea spray and ocean-derived strontium on bioavailable strontium isotope ratios through the analysis of plant samples that were systematically collected along three 200 m-long transects and a hilltop control location. The uninhabited island of Inishark, Co. Galway, Ireland provides a close to pristine setting that allows these findings to be generalized to coastal contexts worldwide. Mixing models are used to interpret the impact of sea spray in comparison to that of the underlying geology and soils. The results highlight the patterned and variable manner in which ocean-derived strontium is taken up by terrestrial plants at varying distances from the coast. We suggest that the morphology of the droplet cloud formed by sea spray as it travels to shore may result in a dead zone, causing less sea spray to land directly next to the sea cliffs. The spatial and isotope data indicate that ocean-derived strontium does not have as great of an impact directly adjacent to the shoreline as it does on the isotope ratios found between 50 and 200 m from the coast. The archaeological implications of this finding include the need for more intensive baseline sampling and increased uncertainty when discussing conclusions about paleomobility in coastal settings.